Síntese e ativação superficial de novos suportes magnéticos para imobilização de enzimas - Kopp, Willian (2013)
Enzymes are potent catalysts, but operationally fragile, expensive and soluble. Industrial applications of enzymes, often, are possible only using immobilized enzyme. Nowadays, various studies have been performed aiming to immobilize enzymes onto magnetic carriers, which allow the selective recovery of the derivative by applying an external magnetic field even in complex reaction media containing other suspended solids. There are many studies using magnetic carriers in enzymes immobilization procedures, however there are no commercially available enzymes immobilized onto magnetic materials. In these studies usually are used carriers with not ideal characteristics for applications in industrial processes. The present study aimed to develop new magnetic carriers and methods for immobilization of enzymes in these carriers, penicillin G acylase (PGA) and cellulases have been used as model enzymes. The thesis was divided into five parts, in the first part (Chapter 1) the state-of-art is presented. The second part (Chapter 2) describes the synthesis of magnetic carriers robust, cheap and with good characteristics for applications in bioprocesses. For this purpose were tested the synthesis of silica magnetic microparticles (SMMps) in water-in-oil micro-emulsion using sodium silicate as silica source and superparamagnetic iron oxide nanoparticles as magnetic core. Materials with good magnetic properties, high surface area and mesoporous structure were obtained. SMMps structure was characterized, it was possible to control the final structure of the material according to the synthesis conditions. In the third part of this study (Chapter 3) was evaluated a new concept in enzymes immobilization using magnetic materials. Magnetic tags were co-aggregated with PGA and cross-linked with glutaraldehyde, producing magnetic cross-linked enzymes aggregates (M-CLEAs). Several reaction conditions were tested producing M-CLEAs with different characteristics and strong response to external magnetic fields. Derivatives with good recovered activity and increased thermal and methanol 50% (v/v) stabilities were obtained. M-CLEAs presented superior performance, in comparison with the free enzyme, in penicillin G hydrolysis experiments, being reused for three reaction cycles without loss of activity. In the fourth part of this study (Chapter 4) the immobilization of the Trichoderma reesei cellulolytic complex onto 17 carriers using 60 different immobilization conditions was evaluated. Covalent methods to cellulases immobilization resulted in total loss of the enzymatic activity. The immobilization by adsorption allowed preserving a portion of the enzymatic activity, however, the enzyme was desorbed from the carrier with the increase in the ionic strength. The best results were achieved for adsorption in MANAE-agarose followed by cross-linking with glutaraldehyde. Hydrolysis experiments using insoluble substrates showed that it is possible to hydrolyze such substrates even using immobilized enzyme onto porous carriers. The derivative was reused for ten reaction cycles (hydrolysis of filter paper) saving more than 90% of its activity. Finally, in Chapter 5, the T. reesei cellulolytic complex was immobilized by adsorption onto SMMp activated with amino groups followed by glutaraldehyde cross-linking achieving good results in terms of recovered activity.